THE ROLE OF CHINESE ENTREPRENEURS IN THE ECONOMY OF KAZAKHSTAN - А., Абaгaнов; Д.Б., Дәуен (Journal of Oriental Studies, 2019)
This article is devoted to the role of Chinese entrepreneurs in the economy of Republic of Kazakh- stan and this topic has a great interest in these days for businessmen of our country. Economic coopera- tion between China and Kazakhstan plays an important role in the development of entire Central Asia region. This article makes an economic review of two countries and examines problems and prospects of trade and economic cooperation between these two countries. Particularly, I’ve tried to determine the role of foreign investment in the economy of Kazakhstan and Chinese entrepreneurs, which could simulate trade turnover and the dynamic development of financial relations in the country. Key words: development, Chinese entrepreneurship, Kazakhstan.